Post‐fire bedload sediment delivery across spatial scales in the interior western United States. Issue 7 (12th November 2013) - Wagenbrenner, Joseph W.; Robichaud, Peter R.
ABSTRACT Post‐fire sediment yields can be up to three orders of magnitude greater than sediment yields in unburned forests. Much of the research on post‐fire erosion rates has been at small scales (100 m2 or less), and post‐fire sediment delivery rates across spatial scales have not been quantified in detail. We developed relationships for post‐fire bedload sediment delivery rates for spatial scales up to 117 ha using sediment yield data from six published studies and two recently established study sites. Sediment yields and sediment delivery ratios (SDRs; sediment delivered at the catchment scale divided by the sediment delivered from a plot nested within the catchment) were related to site factors including rainfall characteristics, area, length, and ground cover. Unit‐area sediment yields significantly decreased with increasing area in five of the six sites. The annual SDRs ranged from 0.0089 to 1.15 and these were more closely related to the ratio of the plot lengths than the ratio of plot areas. The developed statistical relationships will help quantify post‐fire sediment delivery rates across spatial scales in the interior western United States and develop process‐based scaling relationships. Published in 2013. This article is a U.S. Government work and is in the public domain in the USA.